TRPV3 Channels Mediate Strontium-Induced Mouse-Egg Activation - Ingrid Carvacho; Hoi Chang Lee; Rafael A. Fissore; David E. Clapham (Cell Reports, 2013)
In mammals, calcium influx is required for oocyte maturation and egg activation. The molecular identities of the calcium-permeant channels that underlie the initiation of embryonic development are not established. Here, we describe a transient receptor potential (TRP) ion channel current activated by TRP agonists that is absent in TrpV3−/− eggs. TRPV3 current is differentially expressed during oocyte maturation, reaching a peak of maximum density and activity at metaphase of meiosis II (MII), the stage of fertilization. Selective activation of TRPV3 channels provokes egg activation by mediating massive calcium entry. Widely used to activate eggs, strontium application is known to yield normal offspring in combination with somatic cell nuclear transfer. We show that TRPV3 is required for strontium influx, because TrpV3−/− eggs failed to conduct Sr2+ or undergo strontium-induced activation. We propose that TRPV3 is a major mediator of calcium influx in mouse eggs and is a putative target for artificial egg activation.